Analisis Pemikiran as-Shabuni Tentang Poligami Dalam Kitab Shafwatut Tafasir - Wahyudi Wahyudi; Wahyu Nada; Cepi Sutanto; Dedeh Widianengsih; Latipah Pitriani (Program Magister Ilmu Al-Qur'an dan Tafsir, Fakultas Ushuluddin dan Pemikiran Islam, Universitas Islam Negeri Raden Fatah Palembang, 2023)
This article explains polygamy according to the thought of Shaykh Muhammad Ali ash-Shabuni. The purpose of this article is to provide an overview of ash-Shabuni's thoughts on polygamy. The method used in this research is the library research method or Literature Study, supported by other related sources. Polygamy has never been discussed. We can look at it from a socio-cultural point of view to a theology-of interpretation. The author tries to analyze how ash-Shabuni explains his interpretation and his thoughts on QS. al-Nisa (4): 3 and 129 which textually mentions polygamy, The book referred to in this study is the book of tafsir Shafwatut Tafasir, he states in his tafsir that polygamy is not a new innovation in Islam, but has been a common practice among Arabs before Islam, although without clear boundaries. Islam, according to him, provides solutions to imbalances and chaos in society through the Sharia law of polygamy. In addition, the author also presents the opinions of Salafi scholars regarding the law of polygamy, more clearly discussing this polygamy. Keywords: Shafwatut Tafasir, Tafsir Al Quran, ash-Shabuni, Polygamy.